2013
DOI: 10.1002/2013ja019205
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of methods for predicting the arrival of coronal mass ejections at Earth based on multiview imaging

Abstract: [1] We investigate the performance of six methods for predicting the coronal mass ejection (CME) time of arrival (ToA) and velocity at Earth using a sample of nine Earth-impacting CMEs between March 2010 and June 2011. The CMEs were tracked continuously from the Sun to near Earth in multiviewpoint imaging data from STEREO Sun-Earth Connection Coronal and Heliospheric Investigation (SECCHI) and SOHO Large Angle and Spectroscopic Coronagraph (LASCO). We use the Graduate Cylindrical Shell model to estimate the th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(138 citation statements)
references
References 75 publications
(111 reference statements)
10
127
1
Order By: Relevance
“…Observational studies have reported on the pre-eruptive phase of the eruption (e.g., Canou & Amari 2010; Vourlidas et al 2012;Syntelis et al 2016), the triggering of the eruptions (e.g., Zuccarello et al 2014;Chintzoglou et al 2015;Reeves et al 2015), and the propagation of the erupting structures in the interplanetary medium (e.g., Colaninno et al 2013) and toward the Earth (e.g., Patsourakos et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have reported on the pre-eruptive phase of the eruption (e.g., Canou & Amari 2010; Vourlidas et al 2012;Syntelis et al 2016), the triggering of the eruptions (e.g., Zuccarello et al 2014;Chintzoglou et al 2015;Reeves et al 2015), and the propagation of the erupting structures in the interplanetary medium (e.g., Colaninno et al 2013) and toward the Earth (e.g., Patsourakos et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CME acceleration/deceleration is directly observed in heliospheric images from the STEREO mission (e.g. Colaninno et al 2013).…”
Section: Prediction Of Icme Arrival Timesmentioning
confidence: 99%
“…While the only relevant observations for a long time were the CME observations in the corona and in situ measurements at 1 AU, the advent of heliospheric imaging with the STEREO mission enabled researchers in recent years to track CMEs from the Sun to the Earth (see the early review by Rouillard 2011). Heliospheric imaging was used by Colaninno et al (2013) to predict the arrival time of nine CMEs, using the graduated cylindrical shell model to remove projection effects. They employed different extrapolations of the height-time trajectory of the CME front beyond a heliocentric distance of 50 R and achieve a prediction of the shock arrival time near 1 AU within ±13 h for the entire event set, and within ±6 h for the seven (78%) best predictions.…”
Section: Comparison Of Radiative Proxies With Other Tools Of Icme Arrmentioning
confidence: 99%
See 1 more Smart Citation
“…A review on its past, present and future may be found in Svalgaard (2013). However, for planetary space weather still more than for space weather, multi-point observations of the upstream solar wind, and the monitoring of the Sun from several vantage points are essential for properly predicting the impact of geoeffective events such as CMEs and SEPs Lugaz et al 2012;Colaninno et al 2013). These requirements apply equally to planetary space weather.…”
Section: A Need For Multi-point Observations Of the Solar Windmentioning
confidence: 99%